Impelemntasi Metode Montesorri dalam pendidikan Anak Usia Dini - Erlina; Noviani , Dwi (Educatia : Jurnal Pendidikan dan Agama Islam, 2024)
Early childhood is a crucial period in child development, encompassing the time from birth to around eight years old. During this phase, children experience rapid growth, both physically and mentally. The foundation of skills, values, and knowledge established during this time will influence their future development. In this research, a qualitative research design is used. The qualitative approach is chosen because the primary focus of the study is to gain an in-depth understanding of the implementation of the Montessori method, developed by Dr. Maria Montessori. This educational approach values the unique learning styles of children. By emphasizing learning through direct experience and creating a supportive environment, practical, sensory, and academic activities in the classroom are designed to encourage independent learning and help children understand concepts concretely. The Montessori method facilitates a meaningful and sustainable learning process, making it an effective choice in early childhood education.